Outcomes of ultrasound-guided percutaneous microwave ablation versus surgical resection for symptomatic large hepatic hemangiomas - Xiaoyin Tang; Min Ding; Bingwei Lu; Jiachang Chi; Tao Wang; Yaoping Shi; Zhi Wang; Dan Cui; Ping Li; Bo Zhai (International Journal of Hyperthermia, 2019)
Purpose: Microwave ablation (MWA) has become increasingly popular as a minimally invasive treatment for benign and malignant liver tumors. However, few studies have demonstrated the benefits and disadvantages of MWA compared to surgical resection (SR) for large hepatic hemangiomas. This study aimed to evaluate the safety and effectiveness of MWA compared to SR for large (5–10 cm) hepatic hemangiomas. Methods and materials: This retrospective comparative study included 112 patients with large, symptomatic hepatic hemangiomas who had been treated with MWA (n = 44) or SR (n = 68) and followed up for a median of 44 months using enhanced computed tomography (CT) or magnetic resonance imaging (MRI). Intraoperative information, postoperative recovery time, postoperative discomfort and complications and treatment effectiveness between groups were compared using a chi-square test or an independent t-test. Results: The operative time was significantly shorter (31.3 ± 21.76 versus 148.1 ± 59.3 min, p < .001) and the blood loss (10.2 ± 60.6 versus 227.9 ± 182.9 mL, p < .0001) and rate of prophylactic abdominal drainage [1 (2.3%) versus 57 (83.8%), p < .001] were significantly lower in the MWA group than in the SR group. Postoperative recovery of the MWA group in regard to indwelling catheter time, normal diet time, incision cicatrization time and hospital stay (p < .001) was significantly better than the SR group. However, no statistically significant difference in effectiveness was noted between the groups (p = .58). Conclusions: MWA may be as effective as SR, and potentially safer for treating large, symptomatic hepatic hemangiomas. To confirm our findings, large-sample, multicentered, randomized controlled trials are needed.